Preparation of n-type polyaniline/hexagonal boron nitride composites with a large thermoelectric power factor - Ugraskan, Volkan; Ceran, Ebubekir; Yazici, Ozlem (SAGE PUBLICATIONS LTD, 2021)
In the present study, it was aimed to investigate the thermoelectric (TE) properties of polyaniline/hexagonal boron nitride (PANI/h-BN) composites. First, h-BN was synthesized from boric acid and urea. Then, PANI-HCl was synthesized by oxidative chemical polymerization. Finally, the composites were prepared using different weight ratios of h-BN. The composites were characterized using attenuated total reflection accessory attached Fourier-transform infrared spectroscopy, UV-vis spectroscopy, X-ray diffraction, and scanning electron microscopy/energy dispersive X-ray analyzer. TE investigation of the composites showed that the addition of h-BN significantly contributes to the TE properties of PANT-HCl. The addition of h-BN increased the power factor of PANI-HCI from 0.07 mu Wm(-1) K-2 to 143.05 mu Wm(-1) K-2. Furthermore, all the composites showed negative Seebeck coefficients which are the characteristics of n-type semiconductors.
Keywords: Polyaniline; hexagonal boron nitride; thermoelectric; composite; n-type semiconductor; CARBON NANOTUBES; CONDUCTIVITY; PERFORMANCE; NANOSHEETS; TRANSPORT; PROPERTY; FILMS; Materials Science; Polymer Science